Competitiveness and difficulty during physical education classes - Novak Zabukovec, Vlasta (Kinesiologia Slovenica, 2002)
In this article the perceived competitiveness and difficulty during physical education classes will be introduced. Previous researches have confirmed that the perception of classroom climate, and thus also that of competitiveness and difficulty, changes from primary to secondary school, and that gender differences occur as well. In this research we tried to establish which variables significantly differentiate groups of pupils who perceive low or high competitiveness and difficulty. The second goal was practical application of the findings. We used questionnaires for measuring classroom climate, motivation and attitudes in the sample of 1152 pupils from primary and secondary schools. The discriminant analysis was used. Considering the mentioned variables, it confirmed two groups of pupils. The group which perceives a high level of competitiveness and difficulty can be described with the motivational-attitudinal function, which offers the teacher relatively precise guidelines for the work in physical education classes. Competitiveness is related to extrinsic motivation, while difficulty with the intrinsic one. At the same time a new question arises, namely, which pedagogical methods a physical education teacher should employ with the pupils who perceive a lower level of competitiveness and difficulty, since this group does not sufficiently relate to the selected variables.
Keywords: motivacija; raziskave; športna vzgoja; tekmovalnost; težavnost; učenci